Analisis Lingkungan Wilayah Kampung Tua Tanjung Uma - Jeanny Laurens Pinassang; Yessy Christanti Silaban; Rickie Cung; Susanto Susanto (Journal of Architectural Design and Development (JAD), 2021)
The old village is a village that is said to have existed for a long time, even before the city of Batam was founded. One of them is Kampung Tua Tanjung Uma which is located on one of the northern headlands of Batam Island, Lubuk Baja Subdistrict and is also directly opposite the waters of the Singapore Strait. Kampung Tua Tanjung Uma has the potential to become a leading halal destination in batam which can have a good impact on the economy of the surrounding residents if managed properly. Therefore, it is necessary to identify the environment so that it can be managed properly. This type of research is quantitative research and only focuses on the physical indications of the Tanjung Uma Old Village area. Furthermore, the researcher provides recommendations for solutions to overcome problems based on the research.